Performance of Some Arabica Coffee Local Varieties from Gayo Highland - Retno Hulupi; Dwi Nugroho; Yusianto . (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Recently, most of coffee farmers at Gayo highland (Aceh) are planting various of local varieties, namely Timtim Aceh, Borbor, P 88, BP 542A and Ateng Super. Those varieties have been planted to replace S line and Catimor Jaluk varieties which were damaged by leaf rust and root disease. Research on the performance of those varieties was to investigate superior characteristics of each variety and moreover as based to choose the best one as released variety for Gayo Highland. Research finding revealed that Timtim Aceh and Borbor varieties were well adapted to Gayo highland conditions with yielding ability 0.956 ton/ha and 0.909 ton/ha, respectively. Although the highest yield was obtained by Ateng Super variety (1.76 ton/ha green coffee), but not stable, therefore it could not be categorized as superior variety. The previous two varieties also had good cup quality (by standard assesment of Specialty Coffee Association of America), then it could contribute Gayo coffee specialty product. The resistance test for leaf rust disease in the field plantation, showed all varieties demonstrated varying in their resistance. BP 542A variety was the most resistant type, whereas Timtim Aceh and Borbor varieties were moderately. However all varieties become more susceptible if planted at lower altitude, less than 1,000 m asl. The resistance test to coffee berry borer and parasitic nematode showed that Timtim Aceh and Borbor varieties were ranked into almost resistant to resistant. Based on all result of the superior characteristics testing, Timtim Aceh and Borbor varieties were the best one, and it could be proposed to be released as Arabica coffee varieties that suitable at Gayo highland. Key words: Arabica coffee, Gayo highland, local varieties, variety performance, cup quality, yielding, resistant to leaf rust disease